The FiscalTransparency in Romania and Turkey: A Comparative Study - Ionescu, Luminita; BUHUR, Sami (Annals of Spiru Haret University. Economic Series, 2016)
The recent financial crisis had a significant impact on global economy and fiscal transparency all over the world. International Monetary Fund and other international institutions are concerned about fiscal policy, fiscal reforms and fiscal transparency among its member countries. The aim of this paper is to present a comparative study of fiscal transparency in Romania and Turkey, the evolution of fiscal and financial reforms in Romania, and weaknesses in the public system in Romania and Turkey.